2016
DOI: 10.1371/journal.pone.0153718
|View full text |Cite
|
Sign up to set email alerts
|

PBRM1 Regulates the Expression of Genes Involved in Metabolism and Cell Adhesion in Renal Clear Cell Carcinoma

Abstract: Polybromo-1 (PBRM1) is a component of the PBAF (Polybromo-associated-BRG1- or BRM-associated factors) chromatin remodeling complex and is the second most frequently mutated gene in clear-cell renal cell Carcinoma (ccRCC). Mutation of PBRM1 is believed to be an early event in carcinogenesis, however its function as a tumor suppressor is not understood. In this study, we have employed Next Generation Sequencing to profile the differentially expressed genes upon PBRM1 re-expression in a cellular model of ccRCC. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(134 citation statements)
references
References 57 publications
12
118
3
Order By: Relevance
“…A recent study suggested that BAF180 augments the hypoxic response, in contrast to our findings (22). Although we do not understand this discrepancy, the authors of that study used Caki-2 cells engineered to produce wild-type BAF180.…”
Section: -O-bki A704-baf180wtcontrasting
confidence: 99%
See 2 more Smart Citations
“…A recent study suggested that BAF180 augments the hypoxic response, in contrast to our findings (22). Although we do not understand this discrepancy, the authors of that study used Caki-2 cells engineered to produce wild-type BAF180.…”
Section: -O-bki A704-baf180wtcontrasting
confidence: 99%
“…Consistent with a recent report, inducible expression of wildtype BAF180 suppressed the proliferation of Caki-2 cells (SI Appendix, Fig. S3 E and F) (22). However, this effect was not specific to wild-type BAF180 because it was also observed with BAF180 (Q1298*; SI Appendix, Fig.…”
Section: G-j)supporting
confidence: 91%
See 1 more Smart Citation
“…Reports of PBRM1 expression levels in RCC and of its association with poor patient survival are contradictory 146,147 . The precise mechanisms that underlie the oncogenic contribution of PBRM1 mutations in RCC remain to be clarified; however, in addition to its role in regulating genes that control proliferation, such as p21 CIP1 , PBRM1 also regulates the expression of cell-adhesion and cell-signalling molecules such as E-cadherin [148][149][150] (and as such, the subcellular distribution of β-catenin) as well as sister chromatid cohesion 151 . Thus, correct expression of PBRM1 is likely to have important roles in pathways that are frequently dysregulated in cancer and in maintenance of genomic integrity, which is a barrier to tumourigenicity 152 .…”
Section: Histone Modification In Rccmentioning
confidence: 99%
“…The ACHN cell line expresses the protein, but harbors a heterozygous nonsense mutation, while 786-O, 769-P, Caki-1, and A-498 express wild-type PBRM1 [133, 134]. The PBRM1 mutation is also reported in Caki-2 and A-704 lines; loss-of-function gene mutations in A-704 and the deletion in exon 17 of the PBRM1 gene in Caki-2 [135] results in no protein expression [133, 134, 136]. Mutations have also been detected in OS-RC-2 and RCC-ER (see Additional file 1: Table S1 for ref) cell lines; however, the former was reported to express PBRM1 protein [133].…”
Section: Introductionmentioning
confidence: 99%